2010
DOI: 10.1093/brain/awq256
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Go–No-Go performance within the subthalamic nucleus region

Abstract: The basal ganglia are thought to be important in the selection of wanted and the suppression of unwanted motor patterns according to explicit rules (i.e. response inhibition). The subthalamic nucleus has been hypothesized to play a particularly critical role in this function. Deep brain stimulation of the subthalamic nucleus in individuals with Parkinson's disease has been used to test this hypothesis, but results have been variable. Based on current knowledge of the anatomical organization of the subthalamic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
114
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 115 publications
(126 citation statements)
references
References 52 publications
9
114
3
Order By: Relevance
“…Importantly, patients' performance improved when they were tested in the on medication/on stimulation condition several months after surgery. Coherently with our findings, STN-DBS has been found to be associated with deficits in go/no-go tasks (Hershey et al, 2004(Hershey et al, , 2010Georgiev et al, 2016but see van den Wildenberg et al, 2006. To our knowledge, this is the first study in which patients' performance has been assessed before and after surgery in two conditions, and in which lesion and stimulation effects have been disentangled.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 89%
See 1 more Smart Citation
“…Importantly, patients' performance improved when they were tested in the on medication/on stimulation condition several months after surgery. Coherently with our findings, STN-DBS has been found to be associated with deficits in go/no-go tasks (Hershey et al, 2004(Hershey et al, , 2010Georgiev et al, 2016but see van den Wildenberg et al, 2006. To our knowledge, this is the first study in which patients' performance has been assessed before and after surgery in two conditions, and in which lesion and stimulation effects have been disentangled.…”
Section: A C C E P T E D Accepted Manuscriptsupporting
confidence: 89%
“…Moreover, STN-DBS or subthalamotomy in Parkinson's disease can be associated with behavioural and psychiatric problems that reflect deficits in inhibitory control or with the appearance of impulse control disorders (see Jahanshahi et al, 2014;Balarajah & Cavanna, 2013). For instance, several studies in which go/no-go paradigms were used reported that STN-DBS impairs the ability to withhold responses on no-go trials (Hershey et al, 2004(Hershey et al, , 2010Ballanger et al, 2009;Georgiev et al, 2016; but see also van den Wildenberg et al, 2006). To our knowledge, no research until now has examined the role of impulsivity in weight gain after STN-DBS.…”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[87][88][89][90][91]. Such discrepancies in the literature may be explained by more general improvements on the task due to improved motor control [92], dissociable temporal effects of stimulation that result in increased impulsive responding as well as improvements in the engagement of inhibitory processes [93], or differences in the effect of STN DBS on inhibitory control depending on whether the ventral or dorsal STN is stimulated [94].…”
Section: Motor Impulsivity In Parkinson's Diseasementioning
confidence: 99%
“…Anterior cingulate activity was related to the number of errors, whereas the parietal region was related to preparation and execution of the motor response and to errors of commission on no-go trials. Further evidence for the involvement of extra-frontal regions in inhibitory control was provided by a study of patients with Parkinson's disease which showed that the sub-thalamic nucleus was involved in the inhibition of responses on the Go/No-Go Task (Hershey et al 2010).…”
Section: Discussionmentioning
confidence: 99%